Adaptive resilience of roadside trees to vehicular emissions via leaf enzymatic, physiological, and anatomical trait modulations. (15th November 2022) - Kumar, Amit; Singh, Hukum; Kumari, Garima; Bisht, Sarita; Malik, Apurva; Kumar, Narendra; Singh, Manish; Raturi, Asha; Barthwal, Santan; Thakur, Ajay; Kaushal, Rajesh
Abstract: Unplanned urbanization and heavy automobile use by the rapidly growing population contribute to a variety of environmental issues. Roadside plants can mitigate air pollution by modifying their enzymatic activity, physiological and anatomical traits. Plant enzymes, physiological and anatomical traits play an important role in adaptation and mitigation mechanisms against vehicular emissions. There is a significant gap in understanding of how plant enzymes and anatomical traits respond or how they participate in modulating the effect of vehicular emissions/air pollution. Modulation of leaf anatomical traits is also useful in regulating plant physiological behavior. Hence, the present study was conducted to evaluate the effects of vehicular pollution on the enzymatic activity, physiological, and anatomical traits of plant species that grow in forests (S1) and alongside roads (S2-1 km away from the S1 site) during different seasons. The present study examines four commonly found roadside tree species i.e. Grevillea robusta, Cassia fistula, Quercus leucotrichophora and Cornus oblonga . The study found that the activities of catalase and phenylalanine ammonium enzymes were higher in G. robusta species of roadside than control site (S1). Non-enzymatic antioxidants such as flavonoid and phenol were also found in higher concentrations in roadside tree species during the summer season. However, the measured values of physiological traits were higher in Q. leucotrichophora tree species of S1 during the summer season. When compared to the other species along the roadside, Q. leucotrichophora had the highest number of stomata and epidermal cells during the summer season. Hence, we found that tree species grown along the roadside adapted towards vehicular emissions by modulating their enzymatic, physiological, and anatomical traits to mitigate the effect of air pollution. Graphical abstract: Image 1 Highlights: Physiological traits of roadside plants adversely affected by the vehicular emissions. The higher enzymatic activity was found at roadside trees. Leaf anatomical traits were modified at roadside to adapt the vehicular pollution. Roadside trees had developed resistance to withstand against vehicular pollution. Quercus leucotrichophora exhibited higher physiological adaptation.